PENGARUH METODE TALAQQI TERHADAP PRESTASI BELAJAR MATA PELAJARAN TAHFIDZUL QUR’AN - Aini Ainayah; Nur Hidayah; Sugiyat Sugiyat (Raudhah - Proud To Be Professional, 2023)
Talaqqi method is considered as a factor that causes good learning achievement in tahfidzul qur'an subjects of class VIII students. Therefore, the purpose of this research is to find out how strong the influence of the Talaqqi Method is on the Learning Achievement of Tahfidzul Qur'an Subjects. This research uses quantitative research. The sample selected was 55 students of class VIII of Al-Falaah Simo Integrated Islamic Junior High School. Data collection techniques were carried out by distributing questionnaires to students and documentation, Analysis techniques for validity tests using Product Moment, reliability tests using Alpha Cronbach, normality tests using Kolomogorov-Semirnov, linearity tests by comparing the probability value of sig deviation linearity and testing the significance of the correlation coefficient using product moment. These tests are assisted using the SPSS application. The results showed that the talaqqi method was categorized as high or reached 75,53 and the learning achievement of tahfidzul qur'an subjects was in the high category or reached 85,29. The existence of a positive and significant influence between the Talaqqi Method and the Learning Achievement of Tahfidzul Qur'an Subjects is evidenced by hypothesis testing using the product moment correlation formula with the result of 0.86. While the R table at a significant level of 95% is 0.266.